2020
DOI: 10.1111/bph.14958
|View full text |Cite
|
Sign up to set email alerts
|

Different receptor mechanisms underlying phytocannabinoid‐ versus synthetic cannabinoid‐induced tetrad effects: Opposite roles of CB1/CB2 versus GPR55 receptors

Abstract: Background and Purpose Cannabis or cannabinoids produce characteristic tetrad effects—analgesia, hypothermia, catalepsy and suppressed locomotion, which are believed to be mediated by the activation of cannabinoid CB1 receptors. Given recent findings of CB2 and GPR55 receptors in the brain, we examined whether these receptors are also involved in cannabinoid action. Experimental Approach We compared Δ9‐tetrahydrocannabinol (Δ9‐THC)‐, WIN55212‐2‐, or XLR11‐induced tetrad effects between wild‐type (WT) and each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 53 publications
1
26
1
Order By: Relevance
“…This effect may be due to the regulation of extracellular dopamine release in the nucleus accumbens (Li et al, 2021). CB 2 -null mice also have a different response to some tetrad tests compared with wild-type mice, particularly the analgesic and catalepsy tests (Liu et al, 2017(Liu et al, , 2020Wang et al, 2020).…”
Section: Implications Of Different Receptor Potenciesmentioning
confidence: 99%
“…This effect may be due to the regulation of extracellular dopamine release in the nucleus accumbens (Li et al, 2021). CB 2 -null mice also have a different response to some tetrad tests compared with wild-type mice, particularly the analgesic and catalepsy tests (Liu et al, 2017(Liu et al, , 2020Wang et al, 2020).…”
Section: Implications Of Different Receptor Potenciesmentioning
confidence: 99%
“…Effects of THC on temperature appear to mostly be mediated via the CB 1 receptor since the CB 1 antagonist/inverse agonists SR141716 (Rimonabant) and AM-251 have been shown to block effects of cannabinoid agonists such as ∆ 9 -tetrahydrocannabinol (THC) when delivered by parenteral injection (Grim et al, 2017;Taffe et al, 2015) and deletion of the CB 1 receptor in mice prevents hypothermic responses to THC (Wang et al, 2019;Zimmer et al, 1999). Prior studies from this laboratory found that SR141716, administered 15 minutes prior to intraperitoneal injection of THC blocked the body temperature decreases, and tail-flick latency increases (Nguyen et al, 2016b;Taffe et al, 2015;, which is consistent with prior reports that SR141716 pretreatment attenuated a prolactin response to THC (Fernandez-Ruiz et al, 1997) and the hypothermia caused by the CB 1 full agonist WIN 55,212-2 in mice (Son et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The open field test (OFT) was performed to determine whether Mepirapim treatment induces hypomotility. The test used previously reported experimental designs, with minor modifications [36]. The open field was an opaque plastic box (30 × 30 × 30 cm), divided into 16 (4 × 4) equal sectors (7.5 × 7.5 cm).…”
Section: Open Field Testmentioning
confidence: 99%
“…Body temperature ( • C) measurements were taken, with minor modifications of previously reported experimental designs, to determine whether Mepirapim treatment induces hypothermia [36]. After the basal body temperature was measured, mice were treated with the drug.…”
Section: Body Temperature Measurementmentioning
confidence: 99%